Investigação experimental de fatores que modificam parâmetros de dependência e recaída por anfetamina - Segat, Hecson Jesser (2019)
Amphetamine (AMPH) is a psychostimulant drug able to modify the neuroplasticity of areas related to the reward system; for instance, the mesocorticolimbic system. Besides the factors linked to the drug itself, addictive behaviors are also influenced by environment, stress and characteristics belonging to the person, which include sociability, social vulnerability, genetic conditions among others. Currently, the available approaches for the treatment of psychostimulant drug addiction are scarce and palliative, favoring relapses. Considering the external influences on drug addiction and the lack of efficient therapies, the current study evaluated the following factors that can interfere in AMPH addiction: I) the influence that the consumption of trans fatty acids (TFA) together with the practice of physical exercises, observing the drug addiction parameters. Such practice has been related to the reduction in the use of drugs, and the TFA intake has been associated to a higher risk of addictive behavior regarding AMPH. The supplementation with TFA (3g/kg, v.o.) happened before (3 months) and concomitantly to the AMPH conditioning and during the moderate physical exercise phase (running on the treadmill, 10m/s, for 1h, 5 times/week, for 5 weeks). In this experimental protocol, the sedentary animals conditioned with AMPH showed relapse behavior, while the ones that received the supplementation with TFA did not. In addition, the animals that consumed TFA and were AMPH conditioned showed higher anxiety, which was prevented by the physical exercise. These animals presented higher levels of TFA in the tegmental ventral area, striatum and pre-frontal cortex, II) the drug addiction treatment using m-trifluoromethyl-diphenyldiselenide has beneficial effects, which are related to its anxiolytic, antidepressant and antioxidant properties. In this protocol, it was observed that the 14-day treatment (0,01mg/kg) prevented the AMPH relapse without altering the working memory of the animals. The treatment reduced the serotonin uptake in the pre-frontal cortex and reduced the oxidative damages in this brain region as well; III) the use of ultra-diluted and dynamized AMPH (isoterapic), in centesimal scale (10-24 ). In this protocol, the AMPH relapse was reduced, the molecular parameters related to drug addiction (D1R, D2R, tyrosine hydroxylase and dopamine transporter) were modified; besides, the oxidative parameters in the pre-frontal cortex were modulated; IV) comparative evaluation of the moderate physical exercise protocol and the intense one. In this evaluation, the animals were submitted to the swimming test with or without extra weight load during 5 weeks. It was observed that the moderate exercise reduced the drug relapse and anxiety behaviors, while the intense exercise did not. Besides, the moderate exercise increased the levels of BDNF, pro-BDNF and TrkB in the hippocampus. On the other hand, it was observed that the intense exercise reduced D1R, tirosine hidroxilase and increased D2R. The four experimental protocols presented in this work (male, albino Wistar rats) were developed through the AMPH (4,0 mg/kg, i.p.) conditioning of the animals (male, albino Wistar rats). The behavioral analyses combined with the oxidative and molecular changes generate tools that can be useful for the treatment of AMPH addiction and in future contribute to anti-drug treatment protocols.